Benign Central Airway Obstruction - Oberg, Catherine L.; Holden, Van K.; Channick, Colleen L. (Seminars in Respiratory and Critical Care Medicine, 2018)
Benign central airway obstruction (CAO) is responsible for significant morbidity due to dyspnea and impaired quality of life. While iatrogenic causes, including stenosis after endotracheal intubation, tracheostomy tube placement, and surgery, account for the majority of cases of benign CAO, there are a multitude of other causes including infections, inflammatory disorders, extrinsic compression, benign endobronchial tumors, and tracheobronchomalacia. The approach to management depends on the underlying process responsible for the disorder and may include systemic therapy, endoscopic therapy, and surgery. In this review, we aim to provide a general overview of the presentation, evaluation, and management of nonmalignant CAO followed by a more in-depth review of several of the more common causes of this disorder.
Keywords: airway obstruction; benign; bronchoscopy; bronchial stenosis; tracheal stenosis